1999
DOI: 10.14507/epaa.v7n1.1999
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Segregation in Arizona Charter Schools

Abstract: Among the criticisms of charter schools is their potential to further stratify schools along ethnic and class lines. This study addressed whether Arizona charter schools are more ethnically segregated than traditional public schools. In 1996-97, Arizona had nearly one in four of all charter schools in the United States. The analysis involved a series of comparisons between the ethnic compositions of adjacent charter and public schools in Arizona's most populated region and its rural towns. This methodology dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
1
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(147 citation statements)
references
References 17 publications
4
136
1
6
Order By: Relevance
“…As discussed earlier, previous studies at the district and school level have shown that when examined in terms of their local contexts (comparing the racial enrollments of charter schools to that of the surrounding public school district or the closest public school), charter schools are less racially diverse than local public schools and districts (Ascher, Jacobwitz, & McBride, 1999;Cobb & Glass, 1999;Wells, et al, 2000). We recognize that the context of where schools are situated locally, educational funding incentives, and how districts chartering agencies choose to interpret state charter legislation are important considerations that likely influence segregation outcomes.…”
Section: Methodsmentioning
confidence: 96%
“…As discussed earlier, previous studies at the district and school level have shown that when examined in terms of their local contexts (comparing the racial enrollments of charter schools to that of the surrounding public school district or the closest public school), charter schools are less racially diverse than local public schools and districts (Ascher, Jacobwitz, & McBride, 1999;Cobb & Glass, 1999;Wells, et al, 2000). We recognize that the context of where schools are situated locally, educational funding incentives, and how districts chartering agencies choose to interpret state charter legislation are important considerations that likely influence segregation outcomes.…”
Section: Methodsmentioning
confidence: 96%
“…However, some authors have found that charter schools increase racial segregation (Bifulco & Ladd, 2007) and the potential to further stratify schools along racial and socioeconomic profiles, allowing a mechanism to escape racial integration (Cobb & Glass, 1999). Sohoni and Saporito (2009) examine levels of racial segregation in private, charter, and magnet schools.…”
Section: Preferences For Race/ethnicity and The Socioeconomic Composimentioning
confidence: 99%
“…Critics argued that charters would drain public resources away from traditional schools and raised concerns that higher-ability students, white students, and students without special needs would disproportionately shift out of the traditional public school system (Frankenberg and Lee 2003;Fiske and Ladd 2000;Cobb and Glass 1999). The sentiment among Minnesota's Governor and many state politicians, however, was that the idea was at least worth trying, and an amended bill capping the program at eight schools and making districts the only sponsors narrowly passed in 1991 (Kolderie 1998).…”
Section: A a Brief History Of Charter Schools In The United Statesmentioning
confidence: 99%